Global Illumination‐Aware Stylised Shading. (27th November 2021) - Doi, K.; Morimoto, Y.; Tsuruno, R.
Abstract: Our aim is to convert an object's appearance to an arbitrary colour considering the light scattering in the entire scene, which is often called the global illumination. Existing stylisation methods convert the colour of an object with a 1‐dimensional texture for 3‐dimensional computer graphics to reproduce a typical style used in illustrations and cel animations. However, they cannot express global illumination effects. We propose two individual methods to compute the global illumination and convert the shading to an arbitrary colour. The methods reproduce reflections in other objects with the converted colour. As a result, we can convert the colour of illumination effects that have not yet been reproduced, such as soft shadows and refractions.